A influência do valor percebido pelo cliente sobre os comportamentos de reclamação e boca a boca: uma investigação em cursos de pós-graduação lato senso - Costa, Francisco José da (2007)
This dissertation has the customer value as the main subject, and the main purpose was to analyze the relationship of value with complaining and word-of-mouth behaviors. The research is justified for the necessity of a scientific analysis putting the three subjects together, in order to make possible a better comprehension of them as elements of the marketing relationship paradigm. This way, it was done a research on the academic literature of each subject, more extensively on customer value. For each subject, it was appointed: an overall analysis; a discussion about the concepts and the theoretical and practical relevance; the main challenges for academic research; aspects of measurement; and the development of researches on the subject in the Brazilian context. From the literature evaluation, five propositions were developed, what generated two different structural models. Conceptual propositions related to the benefits and sacrifices dimensions related to customer value concept were also put in the models. In order to evaluate the two models, a questionnaire was prepared, and the data collected with students of management lato sensu post graduate courses from Fortaleza. A total of 261 questionnaires were collected, and 248 were used in the analysis. Structural Equation Modeling were used to evaluate the models, and the main results were: related to complaining behavior, it was identified that value perceived influences positively the complaining intention, and the action of complaining; related to word-of-mouth, it was identified that value perceived influences positively the word-of-mouth intention, and also the behavior intensity and favorability. In addition, some difficulties were found relating the value conceptual propositions, both with the benefits and the sacrifices dimensions. From the results, some research recommendations involving the subjects were suggested, as a way to solve the limitations of this research, and to evaluate the problems identified in each one of the subjects.